The purposeful graduate why colleges must talk to students about vocation - Clydesdale, Timothy T. (Timothy Thomas) 1965- (The University of Chicago Press, 2015)
Arguing that the simple: direct, systematic, and creative programs engage undergraduates on the question of purpose, this book shows that thoughtful engagement of the notion of vocational calling by students, faculty, and staff can bring rewards for all those involved: greater intellectual development, more robust community involvement, and more.